Anaerobic co-digestion of industrial waste landfill leachate and glycerin in a continuous anaerobic bioreactor with a fixed-structured bed (ABFSB): Effects of volumetric organic loading rate and alkaline supplementation. (February 2021) - de Castro, Thiago Morais; Arantes, Eudes José; de Mendonça Costa, Mônica Sarolli Silva; Gotardo, Jackeline Tatiane; Passig, Fernando Hermes; de Carvalho, Karina Querne; Gomes, Simone Damasceno
Abstract: Anaerobic co-digestion from industrial waste landfill (IWL) leachate and glycerin was evaluated in a continuous anaerobic bioreactor with fixed-structured bed (ABFSB) under mesophilic conditions (30 ± 1 °C). The ABFSB reactor had a useful volume of 4.77 L. The support medium consisted of polyurethane (PU) foam arranged in an orderly manner. The substrate used corresponded to a mixture of 95% IWL leachate and 5% glycerin (v/v) and the inoculum consisted of flocculent anaerobic sludge. The ABFSB reactor was operated in two phases – the 1 st phase (between the 49 th and the 439 th days of operation): started after the inoculum adaptation and the effect of the increase in the organic loading rate (OLR) was evaluated (2; 3.5; 7.1 and 11.6 gCOD L −1 d −1 ); the 2 nd phase (between the 440 th and 471 st days of operation): the effect of the reduction in alkalinity supplementation via sodium bicarbonate (NaHCO3 ) was evaluated (0.56; 0.42; 0.28; 0.14 gNaHCO3 gCODinfluent −1 and non-supplementation). The OLR of 7.1 gCOD L −1 d −1 was the condition that presented the best results in the 1 st phase for the parameters: maximum methane flow rate (MFR) (7.61 LN CH4 d −1 ), methane yield (MY) (0.30 LN CH4 gCODremoved −1 ), volumetric methane production rate (VMPR) (2.79 LN CH4 L −1 d −1 ), COD removal efficiencies (ERTCOD ) and soluble COD (ERSCOD ) higher than 90%. In the 2 nd phase, the reactor was operated with an OLR of 7.1 gCOD L −1 d −1 and a hydraulic retention time (HRT) of 35.22 h and CODinfluent of 10.68 g L −1 . The minimum alkalinity supplementation required was 0.28 gNaHCO3 gCODinfluent −1, a condition in which the reactor showed stability and satisfactory performance for the parameters: MFR (9.48 LN CH4 d −1 ), MY (0.33 LN CH4 gCODremoved −1 ) and VMPR (3.18 LN CH4 L −1 d −1 ). It was concluded that the ABFSB reactor proved to be stable in the IWL leachate co-digestion and glycerin, when the alkalinity supplementation, effectively necessary, was met. Graphical abstract: Image 1 Highlights: Proportion of 95% of industrial landfill leachate and 5% of glycerin (v/v) was used. A continuous anaerobic bioreactor with a fixed-structured bed (ABFSB) was applied. The highest values of methane obtained in OLR of 7.1 gCOD L −1 d −1 . Removal efficiencies of COD were higher than 90% with HRT of 35.2 h. The minimum alkalinity supplementation required was 0.28 gNaHCO3 gCODinfluent −1 .